MAKNA PENGAMPUAN PERUSAHAAN DALAM HUKUM LINGKUNGAN DITINJAU DARI PRESPEKTIF HUKUM PERDATA - Fitria, Heny Nur; Prasetyawati, Endang (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Basically, everyone can have rights and obligations, but not all people with rights and obligations are able or capable of carrying out their own rights and obligations. Even though it has been regulated in the Civil Code, the Civil Code does not explain further about civil rights that are obtained by people who are under guardianship. The nature of this PPLH law is the legal umbrella for all regulations regarding environmental law in Indonesia. The most important thing in implementing this environmental law policy is fostering strong legislation, prepared as carefully and thoroughly as possible so that there are no mistakes in carrying out environmental law policies by taking into account the elements of integration in the regulatory system, so that effectiveness can be achieved as much as possible. Environmental Protection and Management is a way of realizing and advancing the life and quality of living things. Environmental stewardship, the most important part of achieving the right to a comfortable living environment, is an ideal image of community participation. Natural resources owned by humans today are elements of the environmental order that have become a necessity for every activity carried out in human life